Augmented Reality-Based Mobile Application for Knowledge Transferring in The System of Rice Intensification - Latif, Ummi Khaira; Kusumasari, Tien Fabrianti; Kaewyong, Phuripoj; Duangchant, Shatchaya (International Journal of Innovation in Enterprise System, 2019)
Currently, the System of Rice Intensification (SRI) is one method that can be applied and used to produce seeds of local rice species in highland areas. However, it can currently be seen that the traditional methods to transfer knowledge about SRI from the experts still have limitations in many aspects due to the number of farmers that have experienced success still being low. Some farmers do not have their own fields and it takes a period for farmers to test the rice growing. Currently, mobile devices are widely used in peoples’ lives. Many scholars focus on the application of mobile devices and the augmented reality (AR) technology for the simulation games in many issues while the use of AR-based mobile applications as the learning tools is not widespread. There-fore, in this study, we propose the development of an application on mobile devices with augmented reality technology in order to use it as media in sharing knowledge related to the methods of the System of Rice Intensification by virtual farms simulation. To examine the efficiency of this developed application. A total amount of participants were 512 farmers from 5 regions of Thailand. The experimental results demonstrated that the newly developed AR-based mobile application is effective for improved knowledge on the participants who used the developed application and it can help them to practice their SRI farming skill in the virtual farm simulation. This indicates that the developed AR-based mobile application is the benefits tool for the new knowledge transferring meth-od in the system of rice intensification. For future work, it is necessary to evaluate the farmer success after learning from this AR-based mobile application in order to study the impact of the new method of SRI knowledge transferring. Keywords—augmented reality, knowledge transferring, system of rice intensification.